2016
DOI: 10.15537/smj.2016.9.13599
|View full text |Cite
|
Sign up to set email alerts
|

Role of benign ovarian cysts in the development of adenomyosis

Abstract: Objectives:To assess the association of adenomyotic foci with co-existing benign ovarian cysts.Methods:This prospective cross-sectional study consisted of 100 consecutive hysterectomy specimens referred to Histopathology Section of Pathology Department, Peshawar Medical College, Peshawar, Pakistan by its attached teaching hospitals from January 2011 to December 2012. Hematoxylin and eosin stained sections were examined for adenomyotic foci and the presence of co-existent ovarian cysts. For evaluation of estrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…Adenomyosis may mask other associated pathological conditions as leiomyomas, endometrial or adenomy-omatous Polyps, endometrial hyperplasia and endometritis, so it may cause difficulty in the management 9 . It has been reported that adenomyotic foci were ER positive in 71.5% of cystic follicles and follicular cysts, but all the adenomyotic foci associated with nonfunctional cysts were ER negative 6 . In our study cystic follicles and follicular cysts associated with adenomyosis were 57.1%.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Adenomyosis may mask other associated pathological conditions as leiomyomas, endometrial or adenomy-omatous Polyps, endometrial hyperplasia and endometritis, so it may cause difficulty in the management 9 . It has been reported that adenomyotic foci were ER positive in 71.5% of cystic follicles and follicular cysts, but all the adenomyotic foci associated with nonfunctional cysts were ER negative 6 . In our study cystic follicles and follicular cysts associated with adenomyosis were 57.1%.…”
Section: Discussionmentioning
confidence: 95%
“…The adenomyosis is a common condition in middle aged women, who undergone hysterectomy due to dysmenorrhea, menorrhagia and chronic pelvic pain. In literature it had been reported that incidence and prevalence of adenomyosis is 5-70% [5][6][7] . In our study 39.6% cases were found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation